THREE DREAM: Upaya Meningkatkan Regulasi Emosi, Kecerdasan Emosi, dan Kesehatan Mental Anak Jalanan - Juniarni, Lia; Gunawan, Dwi Agustin Putri; Jannah, Novia Nurul; Khaleda, Rahma Putri; Rustiawan, Dendi; Putri, Mega Maharani Catur (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Mental and emotional health among street children remains an urgent issue in Indonesia due to limited psychosocial support and exposure to daily stressors. This community service program, THREE DREAM (3 Diary Recovery Emotion Actual Mindfulness), was developed as an innovative model combining expressive diary writing and mindfulness training to help children recognize, express, and regulate emotions more effectively. Objective: This study aims to improve emotional regulation, emotional intelligence, and mental health among street children at Yayasan Bagea Bandung through interactive and reflective learning activities. Method: The program was implemented over six offline sessions involving 20 children aged 7–12 years. Each session integrated storytelling, diary writing, drawing, sharing emotions, and mindfulness exercises. Quantitative data were collected using pre-test and post-test questionnaires on three variables: emotional intelligence, emotional regulation, and mental health. The Wilcoxon Signed Rank Test was used to analyze the differences before and after the intervention. Result: The results showed a significant improvement in all measured aspects, with mean emotional intelligence increasing from 64.50 to 82.50, emotional regulation from 21.20 to 33.35, and mental health from 30.90 to 46.75 (p = 0.000). Children exhibited higher self-awareness, confidence, and openness in expressing emotions. Conclusion: The THREE DREAM program effectively enhanced the children’s emotional well-being through creative and mindful activities. This community-based model demonstrates strong potential for replication and sustainability in other social institutions supporting vulnerable children.